1997
DOI: 10.3109/09638289709166047
|View full text |Cite
|
Sign up to set email alerts
|

Single blind randomized controlled trial of visual feedback after stroke: Effects on stance symmetry and function

Abstract: A number of before and after and single case design studies of visual feedback have shown improvements in stance symmetry after stroke, an associated improvement in function has been demonstrated. This study examines this promising technique further using a single-blind controlled trial. Twenty-six patients were recruited from a register of consecutive admissions and randomized into treatment and control groups. Both groups received additional therapy, only the treatment group received visual feedback. Assessm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
91
1
1

Year Published

2002
2002
2018
2018

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 133 publications
(98 citation statements)
references
References 23 publications
5
91
1
1
Order By: Relevance
“…Concurrent augmented visual feedback has also been applied to re-learning balancing tasks among individuals with impaired balance due to neurologic injury (Shumway-Cook et al 1988;Winstein et al 1989;Sackley and Lincoln 1997;Walker et al 2000;Ioffe et al 2010;Sayenko et al 2010;Tsaklis et al 2012) or aging (Wolf et al 1997;Rose and Clark 2000;Lajoie 2004;Sihvonen et al 2004b;Hatzitaki et al 2009). Typically, this is done by asking the participant to stand on one or two force platforms and providing visual feedback regarding weight distribution between the two limbs (Winstein et al 1989;Sackley and Lincoln 1997;Hatzitaki et al 2009), or the location of the centre of gravity (COG; Rose and Clark 2000;Walker et al 2000) or centre of pressure (COP; Shumway-Cook et al 1988;Lajoie 2004;Sihvonen et al 2004b;Ioffe et al 2010;Sayenko et al 2010;Tsaklis et al 2012). With the goal of improving quiet standing balance control when provided with feedback of the COG or COP, participants are asked to minimize movement of the COG or COP (Shumway-Cook et al 1988;Lajoie 2004;Sayenko et al 2010;Tsaklis et al 2012).…”
Section: Introductionmentioning
confidence: 99%
“…Concurrent augmented visual feedback has also been applied to re-learning balancing tasks among individuals with impaired balance due to neurologic injury (Shumway-Cook et al 1988;Winstein et al 1989;Sackley and Lincoln 1997;Walker et al 2000;Ioffe et al 2010;Sayenko et al 2010;Tsaklis et al 2012) or aging (Wolf et al 1997;Rose and Clark 2000;Lajoie 2004;Sihvonen et al 2004b;Hatzitaki et al 2009). Typically, this is done by asking the participant to stand on one or two force platforms and providing visual feedback regarding weight distribution between the two limbs (Winstein et al 1989;Sackley and Lincoln 1997;Hatzitaki et al 2009), or the location of the centre of gravity (COG; Rose and Clark 2000;Walker et al 2000) or centre of pressure (COP; Shumway-Cook et al 1988;Lajoie 2004;Sihvonen et al 2004b;Ioffe et al 2010;Sayenko et al 2010;Tsaklis et al 2012). With the goal of improving quiet standing balance control when provided with feedback of the COG or COP, participants are asked to minimize movement of the COG or COP (Shumway-Cook et al 1988;Lajoie 2004;Sayenko et al 2010;Tsaklis et al 2012).…”
Section: Introductionmentioning
confidence: 99%
“…In such a protocol, the subject stands on a force platform, the COP position is depicted in real time on a computer screen and he/she is required to confine it to the narrowest possible area. This so-called "visual feedback technique" allowed individuals to decrease their postural sway, in both the anteroposterior (AP) and ML directions and is considered an efficient tool in the rehabilitation of patients with impaired balance (17)(18)(19)(20)(21). However, such a technique requires high-cost equipment not often available in rehabilitation or community-living environments.…”
Section: Introductionmentioning
confidence: 99%
“…They assessed sway and stance symmetry, motor and ADL function at 0, 4 and 12 weeks. They concluded that significant improvements were seen in the treatment group in measures of sway, stance symmetry, motor and ADL function, but differences between groups had disappeared at 3 months [39].…”
Section: Discussion:-mentioning
confidence: 99%